Transformational Leadership Training for Vocational School Principals in Ponorogo District : Strengthening Professional Learning Communities - Windasari, Windasari; Trihantoyo, Syunu; Wulandari, Ayu; Fitria, Rezki Nurma (Jurnal Pengabdian UNDIKMA, 2024)
This community service aims to improve the social competence of school principals through transformational leadership training to encourage professional learning communities in the Volatility, Uncertainty, Complexity, and Ambiguity era. The method used in this community service used an IGROW- based coaching approach. The target participants of the training consisted of principals and vice principals of vocational schools in Ponorogo District who were accompanied by coaches from the field of education management with expertise in transformational leadership and educational organizations. The evaluation of this training was conducted using questionnaires. The data collected from these instruments were then analyzed using descriptive statistics. The results of this activity showed that this transformational leadership model training was carried out well and smoothly so that the targets and outcomes of this community service activity could be achieved. Participants were active in conveying and elaborating on the leadership problems faced in their schools. The analysis of the training implementation evaluation data showed that principals were highest in applying the inspirational motivation aspect of transformational leadership. This aspect of inspirational motivation could include the principal's ability to inspire and motivate staff and teachers to achieve the school's vision and goals. This indicates the importance of the principal's role in fostering a positive work environment and motivating their team to achieve better.